Performance-based financing with GAVI health system strengthening funding in rural Cambodia: a brief assessment of the impact. Issue 4 (21st May 2013) - Matsuoka, Sadatoshi; Obara, Hiromi; Nagai, Mari; Murakami, Hitoshi; Chan Lon, Rasmey
Abstract: Introduction Though Cambodia made impressive gains in immunization coverage between the years 2000 and 2005, it recognized several health system challenges to greater coverage of immunization and sustainability. The Global Alliance for Vaccines and Immunization (GAVI) opened a Health System Strengthening (HSS) funding window in 2006. To address the health system challenges, Cambodia has been receiving the GAVI HSS fund since October 2007. The major component of the support is performance-based financing (PBF) for maternal, neonatal and child health (MNCH) services. Objective To examine the impact of the PBF scheme on MNCH services and administrative management in rural Cambodia. Methods Quantitative and qualitative studies were conducted in Kroch Chhmar Operational District (OD), Cambodia. Quantitative analyses were conducted on the trends of the numbers of MNCH services. A brief analysis was conducted using qualitative data. Results After the commencement of the PBF support, the volume of MNCH services was significantly boosted. In addition, strengthened financial and operational management was observed in the study area. However, the quality of the MNCH services was not ensured. Technical assistance, rather than the PBF scheme, was perceived by stakeholders to play a vital role in increasing the quality of the services. Discussion To improve the quality of the health services provided, it is better to include indicators on the quality of care in the PBF scheme. Mutual co-operation between PBF models and technical assistance may ensure better service quality while boosting the quantity. A robust but feasible data validation mechanism should be in place, as a PBF could incentivize inaccurate reporting. The capacity for financial management should be strengthened in PBF recipient ODs. To address the broader aspects of MNCH, a balanced input of resources and strengthening of all six building blocks of a health system are necessary.